Investigation and analysis of a Solar Tracking Panel powered by an Arduino: Developing an automated solar tracking system using Arduino (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The solar panels' efficiency can be improved by identifying various ways to follow the sun'sposition, a work comprised of the discovery of numerous methods of tracking the sun, as well asanalysis. The challenge is to build a system that increases electricity generation by at least 35 and nomore than 45. The control circuit is done using the microcontroller. Once the control circuit hasdetermined the orientation of the solar panel, it next places the motor in order to achieve this bestposition. The project was created to help combat the difficulty of finding affordable, accurate, and powerefficientmicrocontroller-based tracking systems that fit inside an allotted time and budget. It is expectedto automatically track the sun's position in the sky during the day and to greatly reduce the amount ofpower that is used throughout the night. An algorithm has been implemented to solve the motor controland it has been programmed into C on Arduino IDE.